THERAPY CYCLING TO ELIMINATE HIGH-TITERED, MULTIPLE VIRUS INFECTION IN VITRO POT A TO PLANTLETS - Iswari S. Dewi; Steven A. Slack (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1994)
A protocol for treatment of in vitro potato plantlets to eliminate systemic viruses was established. Efficiency decreased, however, for selected genotypes when a virus was high-titered and/or multiple viruses existed Modified nodal cutting (Mncs =